2005
DOI: 10.1667/rr3355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Radiation Tolerance Based on the Induction of DNA Double-Strand Breaks in Tobacco BY-2 Cells and CHO-K1 Cells Irradiated with Gamma Rays

Abstract: Higher plants are generally more tolerant to ionizing radiation than mammals. To explore the radiation tolerance of higher plants, the induction of DNA double-strand breaks (DSBs) by gamma rays was investigated in tobacco BY-2 cells and compared with that in Chinese hamster ovary (CHO)-K1 cells as a reference. This is the first examination of radiation-induced DSBs in a higher plant cell. The resulting DNA fragments were separated by pulsed-field gel electrophoresis and stained with SYBR Green I. The initial y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Dr. Kevin Culligan provided the atr and atr,atm segregating lines. We are extremely grateful to Dr. Steve Jacobsen and members of his lab for sharing histone preparation protocols and technical advice and to Dr. Y. Yokota for sharing in press data (Yokota et al, 2005). We thank Dr. Eli Hefner for ordering the ␥-H2AX peptide and antibody.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Kevin Culligan provided the atr and atr,atm segregating lines. We are extremely grateful to Dr. Steve Jacobsen and members of his lab for sharing histone preparation protocols and technical advice and to Dr. Y. Yokota for sharing in press data (Yokota et al, 2005). We thank Dr. Eli Hefner for ordering the ␥-H2AX peptide and antibody.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Yokota et al performed PFGE (Rydberg et al, 1994;Lobrich et al, 1995;Whitaker et al, 1995) in tobacco BY-2 cells and Chinese hamster ovary (CHO) cells to directly quantitate and compare IR-dependent DSB induction. They determined DSB induction in tobacco cells was only onethird the rate of CHO cells (2.0 Ϯ 0.1 vs. 6.6 Ϯ 0.2 DSBs/ Gy-Gbp; Yokota et al, 2005), and the consistency of their CHO DSB induction data with previously published data suggests their methodology is reliable (Table 3; Cedervall et al, 1995). This suggests that plants are, like yeast and mammals, forming ␥-H2AX foci at DSBs and that the lower rate of focus formation observed in plants is simply due to a lower rate of damage induction by IR.…”
mentioning
confidence: 99%
“…For instance, a comparative study of tobacco BY‐2 and Chinese hamster ovary cells showed that plant cells yielded one‐third less double‐strand breaks after the same dose of ionizing radiation (IR). Furthermore, the plant cells also tolerated a much higher number of DSBs before they died (Yokota et al , 2005). Despite the apparent power and their relevance for agriculture under changing environmental conditions, the plant DNA repair pathways are not very well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for these similarities and differences in the biological action of radiation on plant and animal objects remains unclear, but presumably is associated with DNA repair effectiveness [4].…”
mentioning
confidence: 99%